Analysis of Muslim Friendly Tourism Development in Indonesia - Sugeng Santoso; Ari Ana Fatmawati; Rian Ubaidillah; Winda Widyanty; Salmi Mohd Isa (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
In order to make Indonesia the center of the world's Islamic economy, tourism is one of the potential sectors to be developed. The objectives of this study are; to obtain a description of the existing conditions of Muslim friendly tourism and to formulate certain programfor the Ministry of Tourism and Creative Economy (Kemenparekraf/ Baparekraf). Those institutions arepolicy makers, related to developing the Muslim-friendly tourism businesses ecosystem. This study is qualitative, but some data is collected through quantitative approach. The key informant are policy makers at the Kemenparekraf/Baparekraf. The facilities which is needed are places of worship, food and beverage services that are Muslim-friendly,and the availability of travel agencies that offer Muslim-friendly travel packages. Labeling of halal certification on food and beverage processing that applies the CHSE (Clean, Health, Safety, Environment) standard is a strategy offered on the demand side. On the linkage side, the development of tourism must involve several administrative areas. Beside that, it is necessary to increase education to the community, and it must be in accordance with applicable customary regulations. Every tourism destination also needs segmentation and product development, that always adapts to the trends.